Socioeconomic inequalities and exposure to traffic-related air pollution in the city of São Paulo, Brazil - Mateus Habermann; Míriam Souza; Rogério Prado; Nelson Gouveia (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
Air pollution is a leading public health concern. In addition, poor populations have been reported as showing increased exposure to such pollution. The current study thus aimed to evaluate the socioeconomic status of the population exposed to vehicle-related air pollution in the city of São Paulo, Brazil. The study used data from the 2010 Census on head-of-household's mean monthly income and the percentage of households connected to the sewage system. Exposure to air pollutants was estimated according to traffic density in the census tract plus a 200m surrounding buffer. The relationship between exposure and socioeconomic variables was analyzed by the Kruskal-Wallis test. Exposure increased with increasing socioeconomic status (p < 0.001). The population with the highest socioeconomic status lives in the most polluted areas of the city. However, place of residence alone is not capable of measuring exposure. The study suggests that future epidemiological studies include other indicators of vulnerability.